Well, darling, to get that equation in slope-intercept form, you just need to solve for y. So, rearrange the equation to get y = (2/6)x - 3/2. And there you have it, sweetie, the slope-intercept form of 2x - 6y = 9 is y = (1/3)x - 3/2.
Chat with our AI personalities
Slope-Intercept Form: y = -2x +1
y - d = cx so d = - cx + y That is the slope-intercept form in the c-d plane. Slope = -x Intercept = y
y=2.6x+0(this is in slope intercept form already)(slope intercept form is y=mx+b)m=slopeb=y-interceptso the slope is 2.6
If: 11x-8y = 32 Then: -8y = -11x+32 And: y = 1.375x-4 in slope-intercept form
It is slope intercept form. The equation for slope intercept form is y=mx+b which is like your equation y=5x+6